Analisis Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi Dalam Mengikuti Program Brevet Pajak : Kajian Terhadap Pengetahuan Perpajakan, Motivasi Karir dan Persepsi Mahasiswa Pada Perguruan Tinggi Swasta Di Wilayah Bogor - Nurlela; Farizka Susandra; Saepul Anwar (Politeknik Raflesia Press, 2025)
— This research aims to examine the influence of tax knowledge, career motivation, and students’ perceptions on the interest of accounting students in enrolling in the tax brevet program, as well as to analyze whether there are differences in these factors between accounting students at private universities (PTS) with Accreditation A and those at PTS with Accreditation B. The population in this study comprises accounting students at Universitas Djuanda, Universitas Pakuan, IBI Kesatuan, and Universitas Nusa Bangsa. A total sample of 629 students was selected using purposive sampling and the Slovin formula, resulting in 90 samples used for the analysis. Data analysis techniques were conducted using SmartPLS version 3.0 software and an independent sample t-test using SPSS version 22. The research findings reveal that both career motivation and student perceptions have a positive influence on the interest of accounting students in enrolling in the tax brevet program, while tax knowledge does not influence their interest. The independent sample t-test demonstrates that there is a difference in interest between accounting students at PTS with Accreditation A and those with Accreditation B, indicating that the interest in attending the tax brevet program is higher among students at PTS with Accreditation B compared to those at PTS with Accreditation A.